Gut Microbial Community and Host Thermoregulation in Small Mammals - Zhang, Xue-Ying; Wang, De-Hua (Frontiers in Physiology, 2022)
The endotherms, particularly the small mammals living in the polar region and temperate zone, are faced with extreme challenges for maintaining stable core body temperatures in harsh cold winter. The non-hibernating small mammals increase metabolic rate including obligatory thermogenesis (basal/resting metabolic rate, BMR/RMR) and regulatory thermogenesis (mainly nonshivering thermogenesis, NST, in brown adipose tissue and skeletal muscle) to maintain thermal homeostasis in cold conditions. A substantial amount of evidence indicates that the symbiotic gut microbiota are sensitive to air temperature, and play an important function in cold-induced thermoregulation, via bacterial metabolites and byproducts such as short-chain fatty acids and secondary bile acids. Cold signal is sensed by specific thermosensitive transient receptor potential channels (thermo-TRPs), and then norepinephrine (NE) is released from sympathetic nervous system (SNS) and thyroid hormones also increase to induce NST. Meanwhile, these neurotransmitters and hormones can regulate the diversity and compositions of the gut microbiota. Therefore, cold-induced NST is controlled by both Thermo-TRPs—SNS—gut microbiota axis and thyroid—gut microbiota axis. Besides physiological thermoregulation, small mammals also rely on behavioral regulation, such as huddling and coprophagy, to maintain energy and thermal homeostasis, and the gut microbial community is involved in these processes. The present review summarized the recent progress in the gut microbiota and host physiological and behavioral thermoregulation in small mammals for better understanding the evolution and adaption of holobionts (host and symbiotic microorganism). The coevolution of host-microorganism symbionts promotes individual survival, population maintenance, and species coexistence in the ecosystems with complicated, variable environments.